(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the linguistic and cultural characteristics of words that have entered the Uzbek language from Indo-European sources. Through an interdisciplinary approach, we analyze the historical, semantic, and sociocultural aspects of these loanwords, shedding light on the intricate process of language contact and adaptation.